Effect of using colemanite waste and silica fume as partial replacement on the performance of metakaolin-based geopolymer mortars - Uysal, Mucteba; Al-mashhadani, Mukhallad M.; Aygormez, Yurdakul; Canpolat, Orhan (ELSEVIER SCI LTD, 2018)
In this work, metakaolin was partially replaced with two waste materials and the effect of adding those materials on the behavior of the resulted geopolymer composites was investigated regarding physical properties. A comparison was then made between non-fibrous samples and polypropylene fiber reinforced ones in terms of ultrasonic pulse velocity, abrasion resistance, flexural and compressive strength tests together with scanning electron microscopy (SEM) and XRD analyses. In general, results revealed the fact that replacement materials proved to be beneficial. When compared to control sample, colemanite and silica fume samples yielded an improvement of 14.61% and 29.44% in flexural strength, 2.02% and 11.48 in compressive strength, 10.59% and 20% in abrasion resistance. Addition of polypropylene fibers generally helped in improving flexural strength and abrasion resistance of the samples. Microstructural analysis showed a good degree of geopolymerization of the resulted matrix. Colemanite represents a potential usable material in the geopolymer technology especially in Turkey which possesses the world's largest boron reserves. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Geopolymer; Metakaolin; Colemanite; Silica fume; Polypropylene fibers; Abrasion resistance; COMPRESSIVE STRENGTH; FLY-ASH; TEMPERATURE; SHRINKAGE; EVOLUTION; CONCRETE; BINDERS; PASTES; STEEL; Construction & Building Technology; Engineering; Materials Science